Solicitation of HPLC and HPTLC Techniques for Determination of Rutin from Polyalthia longifolia Thwaites - Doshi, Gaurav Mahesh (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Polyalthia longifolia Thwaites is an important traditional plant in India. Rutin, an active constituent has been reported to possess good amount of pharmacological as well as therapeutic potential. OBJECTIVE: The aim of the present study was to find out by analytical techniques how much percentage of rutin is present in the plant leaves’ ethanolic extract by analytical techniques. MATERIALS AND METHODS: Shade dried leaves of Polyalthia longifolia were subjected to cold ethanolic extraction followed by monitoring the isolated rutin high-pressure liquid chromatography (HPLC) and high performance thin layer chromatography (HPTLC) after carrying out preliminary phytochemical screening. RESULTS: Extraction yield was found to be 13.94% w/w. Phytochemical screening of the extract showed the presence of flavonoids, steroids, diterpenoids, alkaloids, saponins, tannins and phenolic compounds and mucilage. From the Rf value, the ethanolic extract was found to be having constituent identical to rutin. By HPTLC and HPLC the amount of rutin was found to be 11.60% w/w and 4.03% w/v, respectively. CONCLUSION: The active constituent isolated was found to be equal to rutin.